THE EFFECT OF SERVICE QUALITY ON CUSTOMER LOYALTY AT THE JEABELLA AESTHETIC CLINIC IN PENGAYOMAN MAKASSAR - Aulia, A. Farah; Natsir, Uhud Darmawan; Burhanuddin; Idris, Abdi Akbar; Musa, Muh. Ichwan (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine how the effect of service quality on customer loyalty at the jeabella aesthetic clinic beauty clinic in pengayoman Makassar. The number of samples used was 81 customers who came to visit the jeabella aesthetic clinic. Data collection was carried out using interview, observation and questionnaire methods. The data analysis technique used is simple linear regression analysis using Statistical Product And Service Solution (SPSS). The results showed that Service Quality (X) had a positive and significant effect on Customer Loyalty (Y) at the jeabella aesthetic clinic beauty clinic in pengayoman Makassar. This means that if there is an influence of good service quality, customer loyalty will be created.